GAMBARAN LONELINESS WANITA DEWASA MADYA TUNANETRA - Muhammad Iqbal Pahlevi; Nur’aeni Nur’aeni (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study aims to explore the phenomenon of Loneliness among middle-aged blind women. The research is driven by the social and emotional experiences of blind women who often face rejection, neglect, and limited social relationships, all of which significantly impact their psychological well-being. A qualitative approach with a phenomenological method was used to uncover the meanings behind the participants’ lived experiences of Loneliness. The participants consisted of three middle-aged blind women selected through purposive sampling. Data were collected through in-depth interviews. The findings reveal that the experience of Loneliness among middle-aged blind women is marked by feelings of rejection, being unacknowledged, disappointment in social relationships, and a desire to withdraw. These conditions are accompanied by negative emotional responses such as hopelessness, impatience, self-condemnation, and mild depression. Contributing factors include abandonment by spouses, rejection from the surrounding environment, and a lack of social support. These findings highlight the importance of emotional support, social acceptance, and spiritual empowerment as integral parts of psychological recovery for individuals with visual impairments